A New Birth of Freedom - Hodder, Maximilian (Tufts Archival Research Center, 2006)
Maximilian Hodder describes his experiences in prewar Poland, as a prisoner sent to a Siberian concentration camp, and as an immigrant to America, and summarizes his beliefs with the conviction that humanity is more good than evil, that individuals have a right to live the life of their choice, and that he has the responsibility to work to end oppression.